Antigua and Barbuda. Significant achievements 2022 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2023)
The activities carried out by the Antigua and Barbuda Delegation of 2022 are identified, focus to needs and interests of the country such as; it coordinated and implemented the rehabilitation of a community garden, thereby supporting an innovative climate smart project; assisted students and teachers to participate in the IICA Youth Farm programme; It supported a regional initiative proyect about climate adaptation resilience to adopt nature-based solutions to reduce non-climate stressors that contribute to land degradation; it supported apiculture management and queen been rearing; it supported local NGOs, in securing external resources for project funding; it conducted a stakeholder workshop to evaluate emergency response plans for two plant pests of regional and national priority; among other.